TRENDS AND OUTCOMES IN FLIPPED LEARNING-BASED INSTRUCTION IN TEACHING READING: SYSTEMATIC LITERATURE REVIEW - Pilu, Reski; Nur, Sahril (LLT Journal: A Journal on Language and Language Teaching, 2023)
Despite the flipped learning growing popularity, empirical research to increase students' reading abilities is still lacking. The majority of research concentrates on students' impressions of the English language rather than particular language abilities. If there is, speaking, listening, and writing is dominant. This systematic literature review summarizes study findings on trends and outcomes of flipped learning-based instruction in teaching reading. The identification, screening, feasibility, and inclusion phase found thirty-one articles between 2015 and 2022 from the Scopus database with a premium Scopus account to access all sources without limits. The results showed that the research trend of flipped learning in teaching reading was less attractive to researchers than other English skills. It can be seen from the lack of publications from year to year and even tends to decline until May 2022. Further research on flipped learning in teaching reading can enrich the literature on knowledge. In addition, Flipped Learning has positive outcomes in influencing students' performance, especially if combined with other methods. For future research, several different research scopes can be considered, such as creating models or designs to apply flipped learning to students' reading performance and comprehension.